Are Bone Bruise Characteristics and Articular Cartilage Pathology Associated with Inferior Outcomes 2 and 6 Years After Anterior Cruciate Ligament Reconstruction?. (April 2017) - Lattermann, Christian; Jacobs, Cale A.; Reinke, Emily K.; Scaramuzza, Erica A.; Huston, Laura J.; Dunn, Warren R.; Spindler, Kurt P.
Objective: To determine (1) if bone bruise characteristics seen on magnetic resonance imaging are associated with patient-reported outcomes prior to and following anterior cruciate ligament reconstruction and (2) if the combined presence of bone bruises with articular cartilage pathology results in inferior 2- or 6-year outcomes. Design: Bone bruise volume and severity were measured on 81 patients' preoperative magnetic resonance imaging in the medial and lateral femoral condyle (MFC, LFC) and medial and lateral tibial plateau (MTP, LTP) using the Costa-Paz classification and a modified version of Roemer and Bohndorf's technique. The relationships between bone bruise volume and severity with Knee Injury and Osteoarthritis Outcome Score (KOOS) and International Knee Documentation Committee (IKDC) scores were assessed, and pre- and postoperative KOOS and IKDC scores were compared between those with bone bruises either with or without combined local articular cartilage pathology. Results: All 81 patients had a bone bruise in at least 1 region and 70 (86%) had bone bruises in ≥2 regions. LTP bruises were the most common (76/81, 94%), followed by the LFC (66, 81%), MTP (46, 57%), and MFC (20, 25%). Neither bone bruise volume nor severity was associated with inferior postoperative outcomes. The subset of 17 patients with bone bruises and combined articular cartilage pathology were 3.4 times more likely to be symptomatic at 6-year follow-up than those without articular cartilage pathology ( P = 0.04). Conclusions: The volume and severity of preoperative bone bruises alone were not associated with 2- or 6-year outcomes; however, bone bruises combined with local articular cartilage pathology appear to be more symptomatic after ACL reconstruction.